The Cambrian Kalkarindji Large Igneous Province: extent and characteristics based on new 40Ar/39Ar and geochemical data - Evins, L.Z.; Jourdan, Fred; Phillips, D. (Elsevier Science BV, 2009)
The Early Cambrian Kalkarindji Continental Flood Basalt Province in northern Australia is an important Large Igneous Province (LIP) both in size and timing. Being the earliest Phanerozoic LIP it may have had a severe effect on the Early Cambrian biota. Here, we investigate the extent of this province by testing the hypothesis that the extensive Table Hill Volcanics in south-central Australia are a southern extension of the Kalkarindji province. The Table Hill Volcanics have long been considered coeval with the Antrim Plateau Volcanics and related volcanics in the Kalkarindji province; however precise age data is lacking. Here, we present new 40Ar/ 39Ar geochronological, and major and trace element data to investigate this possibility. One Table Hill sample yielded a plateau age of 504.6±2.5 Ma (2σ), within error of recently published age data from the Kalkarindji LIP. Samples from both the Table Hill Volcanics and the northern part of the province are low-Ti tholeiites with MgO-content ranging from 3 to 9 wt.% and all samples are highly enriched in incompatible elements compared to primitive mantle. This, coupled with a negative Nb anomaly, suggests crustal contamination at an early stage in magma evolution or a significant contribution from the sub-continental lithospheric mantle. Subsequent fractionation produced further elevation of the REE in the later stages of the eruptions. Subtle differences in some incompatible element ratios between the Table Hill Volcanics and the northern Kalkarindji indicate some variation likely related to the assimilated crustal component or minor mantle source heterogeneity. The new geochronology data and analogous geochemical signatures confirm that the Table Hill Volcanics are a southern counterpart of the Kalkarindji province. These new data permit the areal extent of the province to be estimated at N2.1×106 km2. This makes the Kalkarindji province one of the largest LIPs of the Phanerozoic. Volatile outgassing from a province of this size is likely to have had a significant impact on the climate and biosphere and may have played a dominant role in the Lower–Middle Cambrian mass extinction.